Transthoracic fine-needle aspiration of the lungs, and bacterial culture with antimicrobial susceptibility testing used in diagnosing bacterial pneumonia in dogs and cats: 14 dogs and 2 cats (2009–2021) - Preibisz, Aleksandra; Schwedes, Claudia Sabine (Frontiers in Veterinary Science, 2025)
Transthoracic fine-needle aspiration of the lungs (TFNA) combined with positive bacterial culture is used less frequently than airway lavage in diagnosing bacterial pneumonia in dogs and cats. This retrospective study evaluated TFNA results and bacterial culture findings in 14 dogs (1 dog twice) and two cats with bacterial pneumonia. Bacterial culture yielded positive results in 9/16 (56.3%) of samples. Only 1/11 (9.1%) of isolated bacterial species showed resistance to empiric treatment (amoxicillin with clavulanate). Six patients without prior antimicrobial treatment had negative bacterial cultures, despite the presence of intracellular bacteria on cytology samples. For patients with suspected bacterial pneumonia, we should consider performing both cytological examination and bacterial culture of lung aspirates, with careful interpretation of the results. Bacterial culture should be considered regardless of ongoing or previous antibiotic treatment, and even in cases where intracellular bacteria are not identified on cytology. Based on our antimicrobial susceptibility findings, first-line empirical treatment with amoxicillin with clavulanate might be an appropriate choice in most of cases regardless of the previous treatment.